2012
DOI: 10.1080/15226514.2011.604693
|View full text |Cite
|
Sign up to set email alerts
|

RHIZOSTABILIZATION OF METALS IN SOILSUSING LUPINUS LUTEUSINOCULATED WITH THE METAL RESISTANT RHIZOBACTERIUMSERRATIASP. MSMC541

Abstract: The aim of this work was to test Lupinus luteus plants, inoculated with metal resistant rhizobacteria, in order to phytostabilise metals in contaminated soils. The resistance to heavy metals of strains isolated from nodules of Lupinus plants was evaluated. The strain MSMC541 showed multi-resistance to several metals (up to 13.3 mM As, 2.2 mM Cd, 2.3 mM Cu, 9 mM Pb and 30 mM Zn), and it was selected for further characterization. Furthermore, this strain was able to biosorb great amounts of metals in cell biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…The direct function of rhizosphere-associated algae is the alteration of metal concentration and/or accumulation within plant tissues, and indirectly they are involved in the increase in the root/shoot biomass. Similarly, fungi through antioxidant enzymatic activities alter the biochemical and physiological processes of plant tolerance to heavy metals (Rajkumar et al 2012 ;Yamane et al 2004 ;Jiang and Zhang 2002 ;Glick 2010 ;Aafi et al 2012 ;Miransari 2011 ;Ma et al 2011 ;Rajkumar et al 2010 ;Yang et al 2012 ;Wenzel 2009 ).…”
Section: Role and Mechanism Of Algae In Heavy Metal Accumulationmentioning
confidence: 98%
“…The direct function of rhizosphere-associated algae is the alteration of metal concentration and/or accumulation within plant tissues, and indirectly they are involved in the increase in the root/shoot biomass. Similarly, fungi through antioxidant enzymatic activities alter the biochemical and physiological processes of plant tolerance to heavy metals (Rajkumar et al 2012 ;Yamane et al 2004 ;Jiang and Zhang 2002 ;Glick 2010 ;Aafi et al 2012 ;Miransari 2011 ;Ma et al 2011 ;Rajkumar et al 2010 ;Yang et al 2012 ;Wenzel 2009 ).…”
Section: Role and Mechanism Of Algae In Heavy Metal Accumulationmentioning
confidence: 98%
“…When metal phytostabilisation was aimed, bacteria were able to promote plant growth and reduce either plant metal uptake or its translocation to the shoot, thus preventing the impact of metals in plant development and their entrance into the food chain. Thus, several works have reported that phytostabilisation of metal-polluted soils can be positively affected by the inoculation with PGPRs (Glick, 2010;Dary et al, 2010;El Aafi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…and Serratia spp. strains were able to reduce arsenate, but only using cytoplasmic reductase as a resistance mechanism [20, 29, 30]. …”
Section: Resultsmentioning
confidence: 99%